Comparison of fishing nylon and polypropylene in abdominal wall closure (Colombia Medica, 1988)
To compare the usefulness and costs between nylon fishing line and polypropylene, the medical records of 585 patients with abdominal surgery at the Hospital Universitario San Juan de Dios in Cali, Colombia, in whom these two materials were used for abdominal wall closure, were studied.The infection percentages with nylon and polypropylene were: clean surgeries, 2.8% and 2%; clean-contaminated surgeries, 0% and 1.8%; contaminated surgeries, 3.5% and 0%; and dirty surgeries, 3.4% and 4.7%. In the outpatient controls, both groups showed similar frequencies of complications, except for 5 cases of evisceration, all from sutures with polypropylene. Therefore, considering the great inferiority of the costs of sutures with fishing nylon, its use is considered a recommendable alternative.